Pengaruh Pacaran Terhadap Motivasi Belajar Mahasiswa - Manik, Resmin; Silvester Adinugraha (Sekolah Tinggi Pastoral Tahasak Danum Pambelum Keuskupan Palangkaraya, 2024)
This research aims to identify the influence of dating relationships on students' learning motivation in Palangka Raya. Using a quantitative approach with simple regression analysis, the study involved 75 students as samples. Data collection was conducted through questionnaires, interviews, and observations, with analysis using one independent variable and one dependent variable. The results show that 59% of respondents rated dating as good and 41% as very good. Meanwhile, 88% of respondents stated their learning motivation was good and 12% very good. Simple linear regression analysis revealed that dating affects students' learning motivation, albeit with a relatively small contribution of 15.3%. The majority of students' learning motivation is influenced by other factors. Based on these findings, it is recommended that students concentrate more on learning activities, prioritize study time, and build friendships with individuals who have the spirit to succeed. Parents and relatives are expected to increase supervision and support for students who are dating so they can complete their studies on time with satisfactory GPAs and develop emotional, social, and spiritual intelligence.